Advanced Nanoporous Material–Based QCM Devices: A New Horizon of Interfacial Mass Sensing Technology. Issue 20 (2nd September 2019) - Torad, Nagy L.; Zhang, Shuaihua; Amer, Wael A.; Ayad, Mohamad M.; Kim, Minjun; Kim, Jeonghun; Ding, Bing; Zhang, Xiaogang; Kimura, Tatsuo; Yamauchi, Yusuke
Abstract: Mass interfacial processes have been considered as one of the crucial factors supporting fundamental research. Due to the low cost and conceptual simplicity, significant advancements have been achieved in the development of methodologies based on piezoelectric devices for in situ determination of mass changes on the surfaces of deposited materials under various conditions. The introduction of nanomaterials for designing sensors and monitoring systems becomes essential to create advanced detection systems for selective sensing of toxic analytes for environmental remediation. The integration of materials with predesignated nanostructures into sensor devices, such as surface acoustic wave (SAW), quartz crystal microbalance (QCM), and QCM with dissipation (QCM‐D) monitoring, has led to an immense progress in the sensing applications of toxic target analytes at the nanogram range. Here, an overview is introduced of recent advancement in the fabrication of piezoelectric devices for the interfacial mass sensing of targeted chemical vapors and ions through combination with nanoporous materials including mesoporous materials carbon‐based nanomaterials, metal–organic frameworks (MOFs), MOF‐derived nanoporous carbons, Prussian blue (PB) and its analogues (PBA), zeolites and related materials. Challenges and future prospect are also summarized by the advanced QCM technique associated with properties of nanostructured materials. Abstract : Here, an overview is introduced of recent advancements in the fabrication of quartz crystal microbalance (QCM) sensing devices for the interfacial mass sensing of targeted chemical vapors and ions through combination with nanoporous materials, including mesoporous materials, carbon‐based nanomaterials, metal–organic frameworks (MOFs), MOF‐derived nanoporous carbons, Prussian blue, and its analogs (PB and PBA), zeolites, and related materials.